Evaluación topográfica de limas reciprocantes, posterior a la instrumentación de conductos curvos. Estudio ex vivo - Navarrete Llamatumbi, María Teresa (2023)
Objective. To evaluate the wear (roughness) and topographic changes of the Wave One Gold primary and Reciproc Blue R25 files after instrumentation at 3, 6 and 9 uses in curved canals. Methods. Ex vivo study, consisting of 10 new Reciproc Blue R25 and 5 Wave One Gold primary reciprocating files and 46 mandibular first molars with severe curvature. Molars were divided into 2 groups (23 molars in each group): group 1 Reciproc Blue R25/.08 and group 2 Wave One Gold Primary (25/.07). Reciprocating files from the two groups were analyzed with the contact profilometer at 0, 3, 6 and 9 uses. The measurement was made in the apical, middle, and coronal thirds, and in each analysis, 2 files were observed with the Scanning Electron Microscope. Subsequently, the analysis in the SPSS version 26 IBM ® program was performed using t-Student and Anova tests for normality (p<0.05). Results. There is no significant difference between Wave One Gold primary and Reciproc Blue R25 (p>0.05) in any third of the file; however, there is a significant difference in the wear of the file after the ninth use at the three third levels: apical (p<0.001), middle (p=0.05), cervical (p=0.01). Conclusions. Wave One Gold primary and Reciproc Blue R25 files present superficial changes from the instrumentation of four root canals, the greatest deformation of the files occured at the apical level. The greater the use of the files, the greater the wear of the surface.